Free entry, regulatory competition, and globalization - Kaz Miyagiwa; Yasuhiro Sato (Osaka University, Institute of Social and Economic Research (ISER), 2012)
This paper examines the optimal entry policy towards oligopoly in a globalized world. In an open economy free entry is socially suboptimal, but corrective tax policy to curb entry proves insufficient unless internationally harmonized. Thus, while conferring the gains from trade, globalization prevents countries from pursuing the optimal entry policy. When countries are small, the gains from trade dominate the losses from a suboptimal entry policy, but as markets grow the result is reversed, making trade inferior to autarky. Therefore, the need for tax harmonization grows as the world economy grows. This paper also contributes to the international tax competition literature through the discovery of the reverse home market effect.
Keywords: F15; H21; H77; L13; 330; Entry Policy; Excessive entry; Globalization; Regulatory competition; Markteintritt; Optimale Besteuerung; Steuerwettbewerb; Oligopol; Kleine offene Volkswirtschaft; Theorie